Research on Fracture Characteristics and Energy Dissipation of Hard Rock under the Excitation of Ultrasonic Vibration. (23rd December 2022) - Zhang, Lei; Wang, Xufeng; Wang, Jiyao; Yang, Zhanbiao
Abstract : To promote the application of ultrasonic vibration rock crushing technology in underground rock-drilling engineering, it is necessary to investigate the damage and fracture characteristics of hard rock under the excitation of ultrasonic vibration. In this study, the brittle red sandstone was taken as the research object, the rock fracture experiments under the excitation of ultrasonic vibration were carried out, and the macrodeformation of rock samples was monitored by strain gauges. The experimental results show that the strain curve of rock samples under the excitation of ultrasonic vibration can be divided into the compaction stage, elastic deformation stage, and damage stage; with the increase in static load, the maximum intrusion depth and maximum failure depth of rock samples increase exponentially. To study the damage evolution and energy dissipation mechanism of rock samples under the excitation of ultrasonic vibration, a numerical model was established by using particle flow software PFC2D. The results show that the proposed model can effectively simulate the failure characteristics of rock samples under the excitation of ultrasonic vibration. Through the analysis of the displacement field, stress field, and dynamic fracture process of rock samples, the damage and fracture mechanism of rock samples under the excitation of ultrasonic vibration were revealed. In addition, the ultrasonic vibration simulation tests on rock samples were carried out under different static loads, and the number of rock cracks and energy dissipation process were monitored in real time. The results show that static loads can accelerate the initiation and propagation of cracks and improve the utilization rate of rock crushing energy.